Discussing the misnomer: Exploring multidimensional perception to academic dishonesty in Nigeria. Do school attributes really matter? - Usani Joseph Ofem; Eunice Ngozi Ajuluchukwu; Imelda Barong Edam-Agbor; Faith Sylvester Orim; Patricia Aquah; Udeme Akaninyene Umo; Anaiah Solomon; Faith Igu Ogochukwu; Anastecia William Osang; Akpo Cletus Atah; Joy Joseph Obi; Annastasia Iwang Anashie; et al. (International Journal for Educational Integrity)
Abstract The study was centred on examining multidimensional perception of academic dishonesty in Nigeria using three predictors. Cross sectional survey research was carried out using 11,787 students from different universities. Data collections were done using questionnaire and school records. The instrument used for the study undergone thorough validity checks and the reliability was adequately assessed and the coefficient of the sub scales ranged from 0.78 to 0.89. Simple regression, independent t-test and one sample t-test was used for data analysis. Students’ perception of plagiarism, cheating and impersonation was positive but they had a negative perception of fabrication and falsification. School size was not a significant factor in perception of academic dishonesty. Significant mean differences were found in perception of plagiarism, falsification and impersonation based on school location, but urban and rural students had similar perception on cheating and fabrication of data. Similarly, school community relation has negative relation with perception of academic anxiety with low percentage contributions to plagiarism, cheating, and impersonation but school community relations had strong contribution to impersonation. Thus, programmes that will instigate integrate, honesty and discipline in the students. Considering the disparities in rural and urban setting to academic dishonesty, orientations on ethical research and use of technology should be implemented for students.